Job Assessment Through Bioelectrical Measures: A Neuromanagement Perspective - Zito, Margherita; Bilucaglia, Marco; Fici, Alessandro; Gabrielli, Giorgio; Russo, Vincenzo (Frontiers in Psychology, 2021)
During recruitment human resource departments face two challenges: finding the right people for the job and attracting talent. Therefore, the hiring process requires both the ability to communicate a good company brand image and to understand candidates’ characteristics and potential. In the present study we used a neuroscientific approach to measure the candidates’ experience during a job interview. The experiment involved thirty participants that individually took part in a job interview lasting forty minutes. During the experiment their engagement and stress levels were measured in real time through skin conductance and electroencephalographic (EEG) data. From the results we identified both the most stressful phases (the second and the fourth parts, relating to the explanation of the job and remuneration) and the most engaging phases (the first and the third phases, relating to the presentation of the company and the explanation of the career process) of the interview, suggesting implications for the assessment process. This study is a contribution to the field of Neuromanagement, as a neuroscientific approach was applied to management issues, in the light of work and organizational psychology.